2014
DOI: 10.1002/hrdq.21190
|View full text |Cite
|
Sign up to set email alerts
|

Human Resource Development Practices and Employee Engagement: Examining the Connection With Employee Turnover Intentions

Abstract: The relationship between how an employee perceives support for participation in human resource development (HRD) practices, engagement, and turnover intent has been underrepresented in the literature. Using social exchange theory as a guiding framework, this research sought to better understand the possible linkages of HRD practices and employee engagement to turnover intentions. An Internet‐based self‐report survey battery utilizing a four‐stage preparation method was used as the primary data collection tool.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
250
1
19

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(293 citation statements)
references
References 76 publications
(129 reference statements)
23
250
1
19
Order By: Relevance
“…Using a multi-measure approach would allow for the disentanglement of measures from theoretical structures and labels and provide the ability to identify potentially depressed latent nuances, should such wrinkle sexist. This supposition was in line with current theory (Shuck et al, 2014b).…”
Section: Methodssupporting
confidence: 88%
“…Using a multi-measure approach would allow for the disentanglement of measures from theoretical structures and labels and provide the ability to identify potentially depressed latent nuances, should such wrinkle sexist. This supposition was in line with current theory (Shuck et al, 2014b).…”
Section: Methodssupporting
confidence: 88%
“…First, in line with earlier research showing internal consistency reliability of the JES ranged from 0.88 to 0.96 (e.g., Alfes et al, 2012;Basit & Arshad, 2016;Byrne et al, 2016;Chen et al, 2014;He et al, 2013;Rich et al, 2010;Shuck et al, 2014), the JES in the present study showed excellent internal consistency reliabilities well above the cutoff criteria of 0.70 (Nunnally & Bernstein, 1994) for both Pakistan (α = 0.97) and Malaysia (α = 0.95).…”
Section: Discussionsupporting
confidence: 75%
“…Earlier studies utilizing the JES on Western samples have shown good psychometric properties of this scale and supported its three-factor structure (e.g., Alfes, Shantz, Truss, & Soane, 2012;Basit & Arshad, 2016;Byrne, Peters, & Weston, 2016;Chen, Yen, & Tsai, 2014;He, Zhu, & Zheng, 2014;Rich et al, 2010;Shuck, Twyford, Reio, & Shuck, 2014). However, application of the JES in Asia is relatively limited.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, opportunities for development are important for facilitating employee engagement (Bakker & Bal, 2010;Sarti, 2014;Shuck, Twyford, Reio, & Shuck, 2014). Engagement is defined as the authentic, simultaneous expression of one's emotional, cognitive, and physical dimensions of the self whilst performing one's job role (Kahn, 1990).…”
Section: Introductionmentioning
confidence: 99%